Sejarah SMP Al-Azhar Mandiri Palu 1992-2022 - Mohammad Fadel; Haliadi Haliadi; Suyuti Suyuti; Nuraedah Nuraedah; Misna Misna (Departement of Mathematics Education, 2024)
This research aims to solve problems regarding (1) Describing the history of the founding of Al-Azhar Mandiri Middle School Palu, (2) Outlining the carrying capacity of historical values ​​of